Preheated Composite as an Alternative for Bonding Feldspathic and Hybrid Ceramics: A Microshear Bond Strength Study - Grangeiro, Manasses Tercio Vieira [UNESP]; Rodrigues, Camia da Silva [UNESP]; Rossi, Natalia Rivok [UNESP]; Souza, Karina Barbosa [UNESP]; Melo, Renata Marques de [UNESP]; Bottino, Marco Antonio [UNESP] (Quintessence Publishing Co Inc, 2023)
Purpose: To evaluate the bond strength between alternative or conventional luting agents and indirect restorative materials. Materials and Methods: Blocks of a polymer-infiltrated ceramic network (PICN, Vita Enamic) and a feldspathic ceramic (FEL, Vita Mark II) were sliced and divided according to the luting agent: resin cement (PICN-RC, FEL-RC), flowable composite (PICN-FC, FEL-FC), or preheated composite (PICN-PH, FEL-PH). The ceramic surfaces were polished, etched with 5% hydrofluoric acid for 60 s, and then a silane layer was applied. Cylinders of the luting agents were built up on the ceramic surfaces. In half the samples, the microshear bond strength (mu SBS) was tested after 24 h (baseline). The other half was tested after 5000 thermocycles (5 degrees C-55 degrees C) (aging). The failure modes were determined using a stereomicroscope, and the ceramic surfaces were analyzed using a scanning electron microscope. Data were statistically analyzed with two-way ANOVA. Results: Thermocycling reduced the bond strength values of all experimental groups. Regarding FEL, the preheated composite obtained the highest results. Resin cement showed results similar to the flowable composite at baseline and after aging. The highest results of PICN were obtained from the preheated composite followed by resin cement and flowable composite. Significant differences among the three luting agents were observed before and after aging. The most frequent failures among the experimental groups were adhesive and cohesive in the ceramic. Conclusion: Bond strength results indicate that the preheated composite can be an alternative for adhesive cementation when applied on the tested feldspathic ceramic or PICN.
Keywords: bond strength; dental ceramics; adhesion